Applied Aspects of Pedotransfer Modelling in the Soil Physics - Медведєв, В. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2017)
Purpose. To consider some examples of pedotransfer models use. Methods. Statistics, mathematical modeling. Results. On the basis of mass experimental material which is available in a database «Soil properties of Ukraine» are developed linear and nonlinear pedotransfer models for the description of equilibrium bulk of density, soil-hydrological constants and structure. As base parameters in models data of humus contents and physical clay are used. Conclusions.Various applied aspects of pedotransfer modelling mainly in the soil physics are proved, which, we hope, will promote popularization of this perspective direction.